Fraudulent Financial Statements in Mining Sector Companies Listed on the Bei for the Period 2018 – 2021 - Ngurah Pandji Mertha Agung Durya (Journal Markcount Finance, 2024)
This study aims to determine the effect of pressure, opportunity, rationalization, ability, arrogance, and Fraud Confirmation on financial statement fraud in mining sector companies listed on the Indonesia Stock Exchange in 2018-2021. The data used in this study are secondary data obtained from annual reports & reports. annual finance. By using purposive sampling technique, this study has a sample of 19 mining sector companies for 4 years, the observation data obtained is 76. The data analysis technique used is logistic regression analysis using SPSS 20 software. The results of this study indicate that the variables of pressure, opportunity, rationalization, the ability and arrogance to have no influence on fraudulent financial statements in mining sector companies listed on the Indonesia Stock Exchange in 2018-2021. Meanwhile, the variables of confirmation of fraud have an influence on fraudulent financial statements in mining sector companies listed on the Indonesia Stock Exchange in 2018-2021.